Josephson behavior of phase-slip lines in wide superconducting strips - Sivakov, A.; Glukhov, A.; Omelyanchouk, A.; Koval, Yury; Müller, Paul; Ustinov, Alexey (Physical Review Letters, 2003)
The phase slip lines in two different materials was discussed. The Shapiro steps under microwave radiation which showed that the frequency of the order parameter oscillation was equal to Josephson frequency was studied. It was observed that a periodic oscillation of a critical current versus the applied magnetic field was found in the strips with a hole in the middle. The evidences of macroscopic quantum interference across a phase-slip line were also elaborated.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.pephys.joseph